2006
DOI: 10.1002/jnr.20898
|View full text |Cite
|
Sign up to set email alerts
|

Heavy chain of cytoplasmic dynein is a major component of the postsynaptic density fraction

Abstract: A protein with an apparent molecular size of 490 kDa was found in the postsynaptic density (PSD) fraction isolated from porcine cerebral cortices and rat forebrains, and this 490 kDa protein accounted for $3% of the total protein of these samples. Matrix-assisted laser desorption ionization-time of flight mass spectrometric and Western blotting analyses consistently indicated that this 490 kDa protein consisted primarily of the heavy chain of cytoplasmic dynein (cDHC). Immunocytochemical analyses showed that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…For example, semaphorin 3A signaling pathways have been shown to play an important role in the regulation of dendritic spine maturation in cerebral cortex neurons (44,45). Dynein heavy chain is proposed to be a major component of PSD and is present in dendritic spines, raising the possibility that cytoplasmic dynein plays structural and functional roles in the postsynaptic terminal (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, semaphorin 3A signaling pathways have been shown to play an important role in the regulation of dendritic spine maturation in cerebral cortex neurons (44,45). Dynein heavy chain is proposed to be a major component of PSD and is present in dendritic spines, raising the possibility that cytoplasmic dynein plays structural and functional roles in the postsynaptic terminal (46).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the abrogation of these essential functions by the Swl mutation most likely accounts for the late implantation or early gastrulation lethal phenotype in Swl/Swl embryos. Studies have also shown that this motor protein is involved in multiple neuronspecific processes, such as neuronal migration (Sasaki et al, 2000), the growth and development of neuritis (Barakat-Walter and Riederer, 1996), synapse formation (Cheng et al, 2006), as well as axonal transport of microtubules, neurofilaments (He et al, 2005) and organelles (Schnapp et al, 1989). Among them, the axonal transport role of cytoplasmic dynein has recently been associated with motor neuron survival Puls et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that certain PSD proteins, including tubulins, CaMKII␣, CaMKII␤, MAP2, and cDHC, would exit from dendritic spines of cultured rat hippocampal neurons when these neurons are kept at low temperature for a few minutes or treated with drugs either disrupting actin cytoskeleton (87) or with drugs inducing calcium release from internal stores (Cheng and Chang unpublished results). On the other hand, the same treatments do not affect the localization of PSD-95 or glutamate receptors in dendritic spines.…”
Section: Studying Protein-protein Interactions In the Psd By Immunoabmentioning
confidence: 99%
“…The uuPSD sample was then subject to immunoab- sorption by using protein G-magnetic beads containing covalently linked antibodies to CaMKII␣, EF1␣, PSD-95, and ␣-tubulin. It has been reported that CaMKII␣ and ␣-tubulin are abundant in the PSD (61) and that PSD-95 is a major scaffold protein of the PSD (62). EF1␣, a moonlighting protein proposed to regulate the actin and microtubule cytoskeleton (63,64), is also a prominent component in the PSD (19,22,65).…”
Section: Studying Protein-protein Interactions In the Psd By Immunoabmentioning
confidence: 99%
See 1 more Smart Citation